2009
DOI: 10.1177/0040517509338308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plasma Treatment of Wool on the Uptake of Sulfonated Dyes with Different Hydrophobic Properties

Abstract: A wool fabric has been subjected to an atmospheric-pressure treatment with a helium plasma for 30 seconds. X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry confirmed removal of the covalently-bound fatty acid layer (F-layer) from the surface of the wool fibers, resulting in exposure of the underlying, hydrophilic protein material. Dye uptake experiments were carried out at 50°C to evaluate the effects of plasma on the rate of dye uptake by the fiber surface, as well as give a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 25 publications
(48 reference statements)
5
66
0
Order By: Relevance
“…Based on their thermodynamic energy levels, plasmas are broadly classified into thermal (hot) and non-thermal (cold) plasma. Until recently, industrial applications of plasma were mostly confined to material processing and electronics, including etching and deposition, bonding of plastics, and textile dying [21][22][23] induce plasmas at near ambient temperatures and under atmospheric conditions. This approach has demonstrated significant antimicrobial effects for biological applications [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their thermodynamic energy levels, plasmas are broadly classified into thermal (hot) and non-thermal (cold) plasma. Until recently, industrial applications of plasma were mostly confined to material processing and electronics, including etching and deposition, bonding of plastics, and textile dying [21][22][23] induce plasmas at near ambient temperatures and under atmospheric conditions. This approach has demonstrated significant antimicrobial effects for biological applications [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that plasma treatment using inorganic gas (such as argon, helium and oxygen) introduced new active sites on the surface and etched the fibre surface of the polyester and acrylic [42,43]. For wool fibres, partial removal of lipid layer and formation of cysteic acid after plasma was reported, which confers surface wettability and enhances the wicking properties of the fabrics [28,44,45]. Although sampling issues and visualisation of thin polymer films deposited on fibres using scanning electron microscopy are problematic, there was some evidence to suggest that silicon polymer is formed only on the fibre surface of the coated face (hydrophobic face).…”
Section: Fabrics With Asymmetric Wettability By Plasmasmentioning
confidence: 99%
“…The peak attributed to C-N-H bonding deformation around 1520 cm −1 observably decreased compared to the untreated fabric [49], and the peak at 1690 cm −1 corresponding to C=O stretching in -COOH functional group also became flat after the treatment [50]. This can be attributed to the removal of the covalently-bound fatty acid layer (F-layer) from the surface of the wool fibres, resulting in exposure of the underlying, hydrophilic protein material [45]. To further determine surface atomic composition after the treatment, XPS spectra was carried out on the HMDSO plasma polymer coated on a silicon slice by the three-step plasma.…”
Section: Fabrics With Asymmetric Wettability By Plasmasmentioning
confidence: 99%
“…In addition, by using electrolyte in a dyeing bath, slight positive charge was acquired on the fabric surface. This will promote more dye fibre interaction and resulted in more dye uptake percentage [16][17][18]. Levelling agents have been evolved with reactive dyes to overcome the skitteriness of the fibre.…”
Section: Colour Strength and Dye Uptakementioning
confidence: 99%